Forest clearing in rural livelihoods: household-Level global-comparative evidence - Babigumira, R.; Angelsen, A.; Buis, M; Bauch, S.; Sunderland, Terry C.H.; Wunder, Sven (Elsevier, 2014)
This paper examines the factors that influence rural household decisions to clear forestland. We use a large dataset comprising 7172 households from 24 developing countries. Twenty-seven percent of sampled households had converted forest to agriculture during the previous 12 months, clearing on average 1.21 ha. Male-headed households with abundance of male labor, living in recently settled places with high forest cover, unsurprisingly tended to clear more, but regional peculiarities abounded. Households with medium to high asset holdings and higher market orientation were more likely to clear forest than the poorest and market-isolated households, questioning popular policy narratives about poverty-driven forest clearing.